ANALYSIS OF NUTRITIONAL QUALITY AND BIOACTIVE COMPONENTS OF CISSUSROTUNDIFOLIA, CYPHOSTEMMA DIGITATUM AND CISSUS QUADRANGULARIS (VITACEAE) - Sami Asir Al-Robai (Journal of Animal and Plant Sciences, 2024)
Cissusrotundifolia, Cyphostemma digitatum, and Cissus quadrangularis which belong to Vitaceae family are used as local traditional vegetables by local communities in Saudi Arabia and different regions in Asia for nutritional and therapeutic purposes. They were analyzed in this study in order to provide scientific evidence for their usage as nutritional and medicinal herbs. The protein, fat, fibre, cyanogenic glycoside, phytic acid, flavonoid, and tannin contents of the three species differed significantly (P < 0.05). Results from the nutritional analysis revealed the richness of C. rotundifolia leaves in crude protein (14.54%), carbohydrates (52.32%), fats (6.99%), and energy value (330.35 Kcal/100 g). C. rotundifolia and C. digitatum leaves showed comparable amounts of both vitamins C and A. The highest crude fiber was found in C. quadrangularis (23.82%), which also exhibited a good carbohydrate content (57.20%). Calcium was the most abundant mineral in the studied whole leaf extracts, followed by potassium. C. quadrangularis contained the highest concentrations of sodium (236mg/100 g), iron (29 mg/100 g) and the lowest level of magnesium (96 mg/100 g). The concentrations of heavy metals in all samples were below the permissible level in food. In terms of anti-nutritional factors, all extracts had comparatively low levels of cyanogenic glycoside, phytate, alkaloid, and saponin contents. The leaves of C. quadrangularis contained significantly high levels of phenol, flavonoid, tannin, and proanthocyanidin content. C. rotundifolia leaves had a high level of DPPH radical quenching power (IC50 = 52.27 µg/mL) that was comparable to that of the standard (IC50 = 51.47 µg/mL). Inhibitory activities against alpha-amylase significantly varied among the extracts analyzed. The leaves of C. quadrangularis strongly inhibited alpha-amylase, and their impact was close to the effect of acarbose as a standard anti-diabetic agent. The findings revealed that the studied leafy wild plants can be used as a good source of various nutrients and beneficial biochemicals.
Keywords: Cissusrotundifolia; Cyphostemma digitatum; Cissus quadrangularis; nutrients; anti-nutrients; bioactive compounds